دراسة اقتصادية لأثر الأزمة السورية على القدرة التنافسية للبرتقال في الأسواق الخارجية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The study aimed to determine the impact of the Syrian crisis on the competitiveness of Syrian oranges in foreign markets by using economic indicators to determine the competitive situation  and compare with the competing countries of each market. During the two periods: the first was pre-crisis (2006-2010) and the second was within the crisis (2011-2015). The results of the analysis showed that the quantity of Syrian oranges exports comparing with production was poor, despite of high competitive advantage of prices during the two study periods, and decreased Revealed and Specialized comparative advantage of exports and decline from 4 to 2.2 for the first indicator and from 3.5 to 1.9 for the second indicator, reflecting poor investment of this resource since pre- crisis versus other countries exporting oranges. The market share in the Saudi, UAE, Kuwait and Iraq markets also declined, exception Jordan market which maintained its first rank. It declined significantly in the Iraqi market, from 58.5% to occupy the fifth and final rank. In addition to low penetration index of Syrian oranges exports to all export markets during the two study periods, exception of the Iraqi and Jordanian markets, where the penetration index increased during pre-crisis, but it was extremely low in Iraq market from the first to fifth rank in the second period. The study recommended focus on markets of Jordan, Iraq, Russia, and determining the size of domestic demand and surpluses which help to increase quantity of exports annually, thus reducing costs, maintaining price competitiveness and improving quality, and setting up promotional programs and activating the of commercial accessories thus enhance the penetration index of Syrian oranges in new markets and increase research on foreign markets, describe them in terms of consumer requirements and purchasing patterns, and increase export facilities to maximize export quantity and competitiveness of Syrian oranges. هدفت الدِّراسة إلى تحديد أثر الأزمة السورية على القدرة التنافسية للبرتقال السوري في الأسواق الخارجية، من خلال استخدام المؤشرات الاقتصادية لمعرفة الوضع التنافسي مقارنةً بباقي الدول المنافسة في كل سوق، وذلك من خلال فترتين زمنيتين، تمثلت الأولى في سنوات ما قبل الأزمة (2006– 2010)، والثانية بسنوات الأزمة (2011– 2015)، وقد أظهرت نتائج التحليل ضعف كمية صادرات البرتقال السوري مقارنةً بالإنتاج بالرغم من تمتعه بميزة تنافسية سعرية خلال فترتي الدراسة، وانخفاض الميزة النسبية الظاهرية والتخصصية للصادرات وتراجعها من 4 إلى 2.2 بالنسبة للمؤشر الأول، ومن 3.5 إلى 1.9 بالنسبة للمؤشر الثاني، الأمر الذي يعكس ضعف استثمار هذا المورد منذ فترة ما قبل الأزمة مقارنةً بباقي الدول المصدرة للبرتقال. كما تبيَّن انخفاض النصيب السوقي في كل من الأسواق السعودية والإماراتية والكويتية والعراقية باستثناء السوق الأردني الذي حافظ على مرتبته الأولى، حيثُ تراجع في السوق العراقي من 58.5% في المرتبة الأولى، إلى 0.7% ليشغل المرتبة الخامسة والأخيرة. إضافةً لانخفاض معدل اختراق صادرات البرتقال السوري لجميع الأسواق التصديرية خلال فترتي الدراسة، باستثناء السوق العراقي والأردني الذي ارتفع فيهما معدل اختراقه بالمرتبة الأولى خلال فترة ما قبل الأزمة، في حين تأثر بشكل كبير بالأزمة السورية في السوق العراقي وتراجع إلى المرتبة الخامسة. وقد أوصت الدراسة بضرورة التركيز على كل من السوق الأردني والعراقي والروسي، وتحديد حجم الطلب المحلي والفائض الذي يمكن من خلاله زيادة كمية الصادرات سنوياً وبما يُسهم في تخفيض التكاليف والحفاظ على التنافسية السعرية وتحسين جودة المنتج، وإقامة البرامج الترويجية وتفعيل دور الملحقات التجارية بما يعزز معدل اختراق البرتقال السوري لأسواق جديدة، وزيادة الدراسات المتعلقة بدراسة الأسواق الخارجية وتوصيفها من حيث متطلبات المستهلكين وأنماط الشراء، وتقديم التسهيلات التصديرية بما يكفل زيادة كمية الصادرات والقدرة التنافسية للبرتقال السوري.